A Cat May Look upon Descartes: Review of Laurie Shannon, The Accommodated Animal: Cosmopolity in Shakespearean Locales - Kolb, Justin (Humanimalia, 2014)
Laurie Shannon. The Accommodated Animal: Cosmopolity in Shakespearean Locales. Chicago: University of Chicago Press, 2013. 290 pages. 78.00 hb; 26.00 pb; 14.49 Kindle.